Corneal subepithelial monoclonal kappa IgG deposits in essential cryoglobulinaemia. Issue 8 (August 1989) - Kremer, I; Wright, P; Merin, S; Weiss, J; Pick, A I; Kaufman, H
Abstract : A 60-year-old man suffering from photophobia and visual disturbances was found to have bilateral superficial corneal grey-white gelatinous deposits. An abnormal cold-precipitable serum component was found and characterised as homogeneous IgG-kappa immunoglobulin. Corneal immunohistochemical examination revealed subepithelial IgG-kappa deposits, focally replacing Bowman's layer. The patient underwent superficial keratectomy in both eyes with satisfactory visual results.